Antibacterial Effects of Paeonia lactiflora Extract on Oral Microcosm Biofilms - Ji-Won Lim; Min-Kyung Kang; Hee-Eun Kim (Applied Sciences)
The aim of this study was to evaluate the antibacterial effects of Paeonia lactiflora (PL) extract on oral microcosm biofilms and determine its usefulness as a natural alternative to current antimicrobial agents. Oral biofilms were cultivated on hydroxyapatite disks using human saliva for 2 days, following which they were treated with 1.5 mL of distilled water (DW), 30 μg/mL of PL extract, or 0.12% chlorhexidine gluconate (CHX) once daily for 3 days. Antibacterial effects were assessed by measuring red fluorescence intensity (RatioR/G), bacterial viability (RatioG/G+R), and aciduric bacterial counts. RatioR/G was evaluated using quantitative light-induced fluorescence digital imaging. RatioR/G and RatioG/G+R in the PL group were 0.94-fold and 0.73-fold lower than those in the DW group (p < 0.001 and p = 0.011, respectively) and comparable to those in the CHX group (p = 0.356 and p = 0.964, respectively). Aciduric bacterial counts in the PL group were 0.97-fold lower than those in the DW group (p < 0.001), with no significant difference from those in the CHX group (p = 0.892). Thus, the antibacterial effect of PL extract was comparable to that of CHX; this suggests its potential as a natural alternative for managing oral biofilm-associated diseases.